2015
DOI: 10.1021/acsmedchemlett.5b00323
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Potent and Orally Efficacious TGR5 Receptor Agonist

Abstract: TGR5 is a G protein-coupled receptor (GPCR), activation of which promotes secretion of glucagon-like peptide-1 (GLP-1) and modulates insulin secretion. The 2-thio-imidazole derivative 6g was identified as a novel, potent, and selective TGR5 agonist (hTGR5 EC50 = 57 pM, mTGR5 = 62 pM) with a favorable pharmacokinetic profile. The compound 6g was found to have potent glucose lowering effects in vivo during an oral glucose tolerance test in DIO C57 mice with ED50 of 7.9 mg/kg and ED90 of 29.2 mg/kg.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…In the new reports, Kumar et al (2016) shown that TGR5 induced GLP-1 release from pancreatic α cells via an Epac-mediated PKA-independent mechanism. Agarwal et al (2016) also shown the important roles of TGR5 in T2D. All of these studies indicate the important functions of TGR5 in T2D treatment.…”
Section: Tgr5 and Different Diseasesmentioning
confidence: 80%
“…In the new reports, Kumar et al (2016) shown that TGR5 induced GLP-1 release from pancreatic α cells via an Epac-mediated PKA-independent mechanism. Agarwal et al (2016) also shown the important roles of TGR5 in T2D. All of these studies indicate the important functions of TGR5 in T2D treatment.…”
Section: Tgr5 and Different Diseasesmentioning
confidence: 80%
“…Another proposed mechanism by which bile acids may impact hepatocellular energy metabolism is via activation of the G-protein coupled receptor TGR5 which in turn increase deiodinase-2 expression and activation of thyroid hormone. Some TGR5 agonists have been reported to have glucose lowering (Agarwal et al, 2016; Briere et al, 2015) and lipid-lowering (Zambad et al, 2013) effects in rodents, but the effects on NAFLD have not been reported. TGR5 activation promotes gallbladder filling and thus agonists against TGR5 have the potential to promote gallstone formation.…”
Section: Peroxisome Proliferator-activated Receptor Agonists (Ppar’s)mentioning
confidence: 99%
“…Therefore, TGR5 activation provides a promising strategy for treatment of type 2 diabetes mellitus and associated metabolic disorders 10 11 12 . Thus TGR5 has drawn considerable attention from both academia and industry 13 14 15 16 17 18 .…”
mentioning
confidence: 99%